2005
DOI: 10.1158/0008-5472.can-04-4125
|View full text |Cite
|
Sign up to set email alerts
|

Human Anti-CD40 Antagonist Antibody Triggers Significant Antitumor Activity against Human Multiple Myeloma

Abstract: Monoclonal antibodies (mAb) directed against lineage-specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
112
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 39 publications
1
112
0
Order By: Relevance
“…The importance of NF-kB in multiple myeloma is suggested from its involvement downstream of CD40, the tumor necrosis factor (TNF) receptor family member that is expressed in a variety of B-cell malignancies and which is associated with multiple myeloma homing. Consistent with this, monoclonal antibodies to CD40 block CD40L-induced NF-kB activation as well as IL-6 and VEGF secretion in cocultures of multiple myeloma cells and bone marrowderived stromal cells (Tai et al, 2005). Interestingly, multiple myeloma is currently treated with compounds that can block NF-kB activation (Mitsiades et al, 2002a) (see below).…”
Section: Nf-kb In Hematologic Malignanciesmentioning
confidence: 78%
“…The importance of NF-kB in multiple myeloma is suggested from its involvement downstream of CD40, the tumor necrosis factor (TNF) receptor family member that is expressed in a variety of B-cell malignancies and which is associated with multiple myeloma homing. Consistent with this, monoclonal antibodies to CD40 block CD40L-induced NF-kB activation as well as IL-6 and VEGF secretion in cocultures of multiple myeloma cells and bone marrowderived stromal cells (Tai et al, 2005). Interestingly, multiple myeloma is currently treated with compounds that can block NF-kB activation (Mitsiades et al, 2002a) (see below).…”
Section: Nf-kb In Hematologic Malignanciesmentioning
confidence: 78%
“…(95)(96)(97) In the last decade, MFC immunophenotypic characterization of phenotypically aberrant PC has also been suggested to be a valuable tool for the detection of potential therapeutical targets on clonal PC and orientate tailored antibody-based therapies (and subsequent monitoring). Thus, MoAbs targeting the overall PC population (CD138) (98,99) or either growth factor receptors (IL-6 or IGF-1) (100,101) and other cell surface antigens expressed by aberrant PC (CD33, CD40, CD52, or CD74) (102)(103)(104)(105)(106)(107) and specific markers whose expression is restricted to subsets of PC (e.g. CD19, CD20, CD27, or CD117) have been developed and, several of them are currently under evaluation in phase I/II clinical trials (70,71).…”
Section: Utility Of Mfc In MM and Other Plasma Cell Dyscrasiasmentioning
confidence: 99%
“…This results in the inhibition of CD40L-induced growth of myeloma cells in the presence or absence of stromal cells. 102 In addition, lucatumumab is a potent mediator of ADCC. 102 Preliminary data from a phase 1 study in patients with relapsed/ refractory myeloma showed that lucatumumab as a single agent was well tolerated, with one out of nine patients achieving PR and two with stable disease.…”
Section: Cd40mentioning
confidence: 99%
“…102 In addition, lucatumumab is a potent mediator of ADCC. 102 Preliminary data from a phase 1 study in patients with relapsed/ refractory myeloma showed that lucatumumab as a single agent was well tolerated, with one out of nine patients achieving PR and two with stable disease. The MTD was not (yet) reached and grade 1-2 toxicities mainly consisted of chills, nausea, pyrexia and arthralgia, which were most often reported during the first infusion.…”
Section: Cd40mentioning
confidence: 99%